Study of post quantum cryptography (NTRU) - Lam, Jacqueline Ting Yah (Nanyang Technological University, 2021)
Post quantum algorithms are being developed to be an answer to cryptography in the event where powerful quantum computers that can break current public key cryptosystems become a reality. NTRU is one of the post quantum cryptographic algorithms developed that is thought to be resistant to quantum attacks. NTRU is a lattice-based cryptosystem based on the hardness of solving the Shortest Vector Problem. The primary purpose of this project is to study NTRU, and to implement a lattice attack on the cryptosystem to demonstrate how using unsafe parameters could lead to a compromise of the algorithm. A lattice attack on smaller parameters was implemented to retrieve the private key from the public key and ciphertext. The results of the implementation were further used to: 1) examine the significance of parameter on successful lattice attack, and 2) compare the speed between NTRU and RSA.